THE IMPLEMENTATION OF FULL CALL AUCTION ON TRADING VALUE AND PRICE MANIPULATION INDICATOR IN WATCHLIST STOCKS ON THE INDONESIA STOCK EXHANGE - Risna Aulia; Asri Jaya; Nasrullah Nasrullah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This research analyzes the impact of the Full Call Auction (FCA) policy on transaction values and indications of price manipulation in stocks listed on the Special Monitoring Board (PPK) of the Indonesia Stock Exchange (BEI). This policy was implemented to improve market orderliness and protect investors from the risk of manipulation, which commonly occurs in low-liquidity and high-risk stocks. The research questions include whether FCA causes a significant change in trading value and whether FCA can reduce indications of price manipulation as measured by liquidity, information asymmetry, and volatility. The study uses a comparative quantitative approach with an event study design, analyzing 171 PPK companies during the period of November 3, 2023 - August 26, 2025, using saturated sampling. Secondary data was obtained from BEI, including transaction values, bid-ask data, and stock prices, observed for 10 trading days before and after the implementation of FCA. Descriptive analysis results show that the average trading value increased by 24.46% after FCA, but this change was not statistically significant. Based on the Wilcoxon signed-rank test, liquidity and information asymmetry underwent significant changes after FCA, indicating an improvement in market quality and a reduction in information asymmetry among investors. However, volatility did not show a significant difference, meaning FCA has not yet fully stabilized price fluctuations. Overall, FCA is considered quite effective in reducing indications of price manipulation, especially through increased liquidity and decreased information asymmetry, although its impact on trading value and volatility remains limited in the short-term observation period.